Catechin Loaded Poly(lactic-co-glycolic acid) Nanoparticles: Characterization, Antioxidant and Cytotoxic Activity Against MCF-7 Breast Cancer Cells - Turkoglu, Burcu; Mansuroglu, Banu (AMER SCIENTIFIC PUBLISHERS, 2020)
Here we evaluate the cytotoxic and antioxidant properties of Catechin (Cat) loaded nanoparticles (CatNps) on breast cancer cell lines. CatNps were prepared by the modified single emulsion solvent evaporation method. The structural, physical and chemical properties of the CatNps including PLGA-Cat interactions, and surface characteristics, were analyzed by dynamic light scattering (DLS), Fourier transform infrared (FT-IR), and Scanning Electron Microscopy (SEM). The average particle size of CatNps was 190.5 +/- 1.762 nm with an encapsulation efficiency of 10% and zeta potential value of 13.7 +/- 1.258 mV. The CatNps had reaction yield of 43.47 +/- 1.1% and loading capacity of 3.710 +/- 2.6% Treating MCF-7 cells with CatNps for 48 h led to a decrease in cell viability with an of IC50 22.59 mu g/mL. The antioxidant behavior of CatNps was evaluated by the DPPH method in various pH environments (pH 3-, 6-, 7.4-, 9- and 12). Despite the low encapsulation efficiency, CatNps showed significant antioxidant efficacy against DPPH radicals relative to Cat. Our results revealed that CatNps could be used as promising anti-cancer agents due to their enhanced cytotoxic activity, increased bioavailability, and antioxidant properties.
Keywords: Catechin Hydrate; PLGA; Nanoparticle; Cytotoxic Activity; MCF-7; GREEN TEA CATECHINS; OXIDATIVE STRESS; FREE-RADICALS; GROWTH; NANOTECHNOLOGY; ENCAPSULATION; Chemistry; Science & Technology - Other Topics; Materials Science; Physics